Ergonomic mapping of the “electrician” function, in Companhia Paranaense de Energia – COPEL, Northern Maintenance Division - Ciotta, Daniele (2019)
This study presents an ergonomic mapping of the working conditions of electricians at the Companhia Paranaense de Energia - COPEL. With this purpose, the ethnography was applied as the research method and the Nordic questionnaire was used as a complementary technique. Results showed a relationship between the predominance of pain symptomatology and the tasks performed by these professionals, indicating to the company the need to adopt preventive actions and programs concerning the ergonomics of workers.